Capturing the power of seizures: an empirical mode decomposition analysis of epileptic activity in the mouse hippocampus - Molnár, László; Ferando, Isabella; Liu, Benjamin; Mokhtar, Parsa; Domokos, József; Mody, Istvan (Frontiers in Molecular Neuroscience, 2023)
Introduction: Various methods have been used to determine the frequency components of seizures in scalp electroencephalography (EEG) and in intracortical recordings. Most of these methods rely on subjective or trial-and-error criteria for choosing the appropriate bandwidth for filtering the EEG or local field potential (LFP) signals to establish the frequency components that contribute most to the initiation and maintenance of seizure activity. The empirical mode decomposition (EMD) with the Hilbert-Huang transform is an unbiased method to decompose a time and frequency variant signal into its component non-stationary frequencies. The resulting components, i.e., the intrinsic mode functions (IMFs) objectively reflect the various non-stationary frequencies making up the original signal. Materials and methods: We employed the EMD method to analyze the frequency components and relative power of spontaneous electrographic seizures recorded in the dentate gyri of mice during the epileptogenic period. Epilepsy was induced in mice following status epilepticus induced by suprahippocampal injection of kainic acid. The seizures were recorded as local field potentials (LFP) with electrodes implanted in the dentate gyrus. We analyzed 100 s segments that either included a seizure (typical duration 20-60 s) or a seizure free period. Each segment was divided into non-overlapping 1 s long epochs which were then analyzed to obtain their IMF (usually 6), the center frequencies of the respective IMF and their spectral root-mean-squared (RMS) power. Results: Our analysis yielded unbiased identification of the spectral components of seizures, and the relative power of these components during this pathological brain activity. During seizures, the power of the mid frequency components increased while the center frequency of the first IMF (with the highest frequency) dramatically decreased, providing mechanistic insights into how local seizures are generated. Discussion: We expect this type of analysis to provide further insights into the mechanisms of seizure generation and potentially better seizure detection.